FINANCING SOCIAL ENTERPRISES SERVING THE BASE OF PYRAMID : Toward an integrative financing model - Le, Dan Ha (My University, 2023)
Social Enterprises (SEs) have emerged to become change agents, joining forces with governments, philanthropists, and other social actors to solve persistent and large-scale social problems, such as poverty, homelessness, deprivation of basic education, healthcare and so forth. The dual forms of social organisations and the hybridity of goals (economic and social) are found to have positive and negative effects on attracting external resources. Difficulties in accessing funds are reported as one of the main reasons for the fall of social enterprises. This thesis aims to explore how social enterprises can integrate different sources of financing to sustain business and deliver mission. This study focuses specifically on social enterprises serving the base of pyramid markets, aka. the poor and poorest parts of the world. These organizations often operate in a resource-deprived environment and tend to rely on external resource providers to survive, grow, and catalyze social impacts. This research starts off with synthesizing extant literature and the work of other researchers in the field to gain a deeper understanding of the phenomenon. It uses Pfeffer and Salancik’s (1978; 2003) Resource Dependence Theory and Berger and Ubell’s (1998) Financial Growth Cycle Theory as the initial “two-in-one” theoretical framework. This qualitative research uses multiple case studies, collects data from multiple sources, and combines theme-based analysis, inductive and deductive reasoning to generate empirical insights. The study provides mixed opinions on the applicability of these two classic theories. It underlines that social enterprises in this segment need not only external finance as per their growth cycle, but also internal capability building. Therefore, a “three-in-one” theoretical positioning, comprising Dave and Smallwood’s (2004) Organizational Capability Theory, is put forward. Also, an enhanced integrative financing model is introduced to allow these types of social enterprises to acquire external finance and reduce resource dependence more effectively. These are the main theoretical contributions. On the practical front, this study suggests some significant changes for all actors involved to improve the financing landscape since the existing financial instruments do not work to their best advantage. Furthermore, this study offers some avenues for further research to advance research stream on financing social enterprises.

Doanh nghiệp xã hội nổi lên như một tác nhân thay đổi, chung tay với chính quyền, các đơn vị thiện nguyện, và chủ thể xã hội khác, tham gia giải quyết các vấn đề tồn đọng của xã hội, như đói nghèo, vô gia cư, thiếu hụt giáo dục, y tế căn bản v.v. Mô hình “lưỡng tính” của doanh nghiệp xã hội và việc kết hợp hai mục tiêu khác nhau (mục tiêu kinh tế và mục tiêu xã hội) có tác động tích cực lẫn chưa tích cực cho việc thu hút nguồn vốn bên ngoài. Khó khăn trong việc tiếp cận nguồn vốn là một trong những nguyên nhân chính dẫn đến việc các doanh nghiệp xã hội phải dừng hoạt động. Luận án này khai thác cách thức giúp doanh nghiệp xã hội tích hợp các nguồn lực tài chính nhằm duy trì hoạt động kinh doanh và thực hiện sứ mệnh của mình. Nghiên cứu này tập trung chủ yếu vào các doanh nghiệp xã hội phục vụ thị trường đáy kim tự tháp, hay còn gọi là thị trường nghèo và nghèo nhất của thế giới. Các tổ chức này hoạt động trong môi trường thiếu hụt nguồn lực và có khuynh hướng dựa vào các nhà hảo tâm, đầu tư bên ngoài để tồn tại, phát triển và tạo ra tác động xã hội. Nghiên cứu bắt đầu bằng việc tổng hợp các tài liệu và nghiên cứu trước đây để hiểu sâu hơn về đề tài “cấp vốn”. Nghiên cứu sử dụng khung lý thuyết “hai trong một”, kết hợp lý thuyết “Phụ Thuộc Nguồn Lực” của Pfeffer và Salancik (1978; 2003) và lý thuyết “Chu Kỳ Tăng Trưởng Tài Chính” của Berger và Ubell (1998). Trên nền tảng lý thuyết được xây dựng, nghiên cứu định tính sử dụng phương pháp nghiên cứu trường hợp (case study), thu thập dữ liệu từ nhiều nguồn, phân tích theo chủ đề, kết hợp lập luận quy nạp và suy diễn để đưa ra kết luận thực nghiệm. Nghiên cứu đưa ra kết luận trái chiều về tính ứng dụng của hai lý thuyết cổ điển. Kết quả nghiên cứu nhấn mạnh - các doanh nghiệp xã hội trong phân khúc này không chỉ cần nguồn lực tài chính bên ngoài theo chu kỳ tăng trưởng, mà còn cần xây dựng năng lực nội tại. Do đó, lý thuyết “ba trong một”, kết hợp lý thuyết ‘Phát Triển Năng Lực của Tổ Chức” của Dave và Smallwood (2004), và mô hình tài chính tích hợp nâng cao, được giới thiệu - cho phép các doanh nghiệp xã hội tiếp cận nguồn lực tài chính hiệu quả hơn, đồng thời giảm bớt sự phụ thuộc vào nguồn lực bên ngoài. Đây là những đóng góp chính về mặt lý thuyết. Về mặt thực tiễn, nghiên cứu đưa ra những gợi ý thay đổi đáng kể cho tất cả các bên liên quan để cải thiện mặt bằng tài trợ, bởi các công cụ tài chính hiện tại chưa phát huy hết lợi thế. Không những thế, nghiên cứu còn gợi ý một số hướng nghiên cứu sâu hơn, nhằm thúc đẩy đề tài ‘cấp vốn cho doanh nghiệp xã hội’.
Keywords: Social enterprises, the base of pyramid, resource dependence, traditional and novel sources of funding, financing model, financial growth cycle, organizational capability